2021
DOI: 10.30802/aalas-jaalas-20-000049
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Efficacy of a Long-lasting, Highly Concentrated Buprenorphine Solution in Mice

Abstract: Buprenorphine is a commonly used opioid for mitigating pain in laboratory mice after surgical procedures; however, the dosing interval necessary for standard buprenorphine may require treatment every 4 to 6 h to maintain an adequate plane of analgesia. An alternative formulation that provides prolonged plasma concentration with long-lasting effects would be beneficial in achieving steady-state analgesia. We evaluated a long-lasting and highly concentrated formulation of buprenorphine(Bup-LHC) in mice. Pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Providing appropriate analgesia is seen as a moral and ethical imperative in contemporary laboratory animal medicine. Opioids are widely used in laboratory animals because of their potent analgesia, efficacy in a wide range of moderate to severe pain models, parenteral dosage form, high therapeutic index, and well defined, but minimal side effects when used appropriately, including minor effects on immune function when used appropriately 1–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing appropriate analgesia is seen as a moral and ethical imperative in contemporary laboratory animal medicine. Opioids are widely used in laboratory animals because of their potent analgesia, efficacy in a wide range of moderate to severe pain models, parenteral dosage form, high therapeutic index, and well defined, but minimal side effects when used appropriately, including minor effects on immune function when used appropriately 1–5 …”
Section: Introductionmentioning
confidence: 99%
“…Opioids are widely used in laboratory animals because of their potent analgesia, efficacy in a wide range of moderate to severe pain models, parenteral dosage form, high therapeutic index, and well defined, but minimal side effects when used appropriately, including minor effects on immune function when used appropriately. [1][2][3][4][5] Use of BUP is an essential part of the foundation of pain management for non-human primates. Results from an earlier pharmacokinetic (PK) study demonstrated that a single 0.2-mg/kg subcutaneous…”
mentioning
confidence: 99%
“…Weighted κ scores measuring interrater reliability of radiographic scoring of C57BL/6 mice (0.505) indicated moderate agreement between raters. 15 Welfare indices revealed sporadic differences between groups, but no consistent effects (Figures 2 B, D, and E). Nociceptive differences (measured using Von Frey filaments) between right and left legs and locomotion (distance traveled) were not significantly different from baseline at any time point.…”
Section: Resultsmentioning
confidence: 93%
“…Weighted κ scores measuring interrater reliability of radiographic scoring of SCID mice (0.613) indicated moderate agreement between raters. 15 Welfare indices revealed sporadic differences between groups (Figures 3 B, D, and E). No significant differences in nociception were detected between any groups.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation